Pengaruh Store Atmosphere dan Brand Trust Terhadap Keputusan Pembelian Pada Toko Nadhira Napoleon di Pekanbaru - Feby Saptaria Farhani; Mandataris Mandataris (Komunitas Dosen Indonesia, 2024)
Assessing the impact of store atmosphere and brand trust on purchasing decisions at the Nadhira Napoleon souvenir shop in Pekanbaru. This research was conducted in Pekanbaru City, Riau, with a focus on the Nadhira Napoleon souvenir shop. The population studied was visitors or consumers of this shop. Sampling method using nonprobability (accidental sampling). The sample size is determined using the Slovin formula, which produces 100 respondents as a sample. Data was collected by questionnaire and observation. The variables measured include Store Atmosphere, Brand Trust, and Purchase Decisions. Data analysis involves descriptive analysis, evaluating data validity, and hypothesis testing with the F test and multiple linear regression analysis.The research results prove that Store Atmosphere (X1) has positive influence on purchasing decisions (Y), Brand Trust (X2) has positive influence on purchasing decisions (Y), and Store Atmosphere (X1), Brand Trust (X2) has positive influence on purchasing decisions (Y) at Nadhira Napoleon Pekanbaru.